Perceived mother and father acceptance‐rejection predict four unique aspects of child adjustment across nine countries - Putnick, Diane L (Archīum Ateneo, 2014)
Background It is generally believed that parental rejection of children leads to child maladaptation. However, the specific effects of perceived parental acceptance‐rejection on diverse domains of child adjustment and development have been incompletely documented, and whether these effects hold across diverse populations and for mothers and fathers are still open questions. Methods This study assessed children's perceptions of mother and father acceptance‐rejection in 1,247 families from China, Colombia, Italy, Jordan, Kenya, the Philippines, Sweden, Thailand, and the United States as antecedent predictors of later internalizing and externalizing behavior problems, school performance, prosocial behavior, and social competence. Results Higher perceived parental rejection predicted increases in internalizing and externalizing behavior problems and decreases in school performance and prosocial behavior across 3 years controlling for within‐wave relations, stability across waves, and parental age, education, and social desirability bias. Patterns of relations were similar across mothers and fathers and, with a few exceptions, all nine countries. Conclusions Children's perceptions of maternal and paternal acceptance‐rejection have small but nearly universal effects on multiple aspects of their adjustment and development regardless of the family's country of origin.